Effects of Music Therapy on Drug Therapy of Adult Psychiatric Outpatients: A Pilot Randomized Controlled Study - Degli Stefani, Mario; Biasutti, Michele (Frontiers in Psychology, 2016)
Objective: Framed in the patients’ engagement perspective, the current study aims to determine the effects of group music therapy in addition to drug care in comparison with drug care in the treatment of psychiatric outpatients. Method: Participants (n = 27) with ICD-10 diagnoses of F20 (schizophrenia), F25 (schizoaffective disorders), F31 (bipolar affective disorder), F32 (depressive episode) and F60 (specific personality disorders) were randomised to receive group music therapy plus standard care (48 weekly sessions of two hours) or standard care only. The clinical measures included dosages of neuroleptics, benzodiazepines, mood stabilisers and antidepressants. Results: The participants who received group music therapy demonstrated greater improvement in drug dosage relative to neuroleptics than those who did not receive group music therapy. Antidepressants had an increment for both groups that was significant only for the control group. Benzodiazepines and mood stabilisers did not show any significant change in either group. Conclusions: Group music therapy combined with standard drug care is effective for controlling neuroleptic drug dosages in adult psychiatric outpatients who received group music therapy. We discuss the likely applications of group music therapy in psychiatry and the possible contribution of music therapy in improving the psychopathological condition of adult outpatients. In addition, the implications for the patient-centred perspective were also discussed.